2021
DOI: 10.1038/s43705-021-00073-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased microbial expression of organic nitrogen cycling genes in long-term warmed grassland soils

Abstract: Global warming increases soil temperatures and promotes faster growth and turnover of soil microbial communities. As microbial cell walls contain a high proportion of organic nitrogen, a higher turnover rate of microbes should also be reflected in an accelerated organic nitrogen cycling in soil. We used a metatranscriptomics and metagenomics approach to demonstrate that the relative transcription level of genes encoding enzymes involved in the extracellular depolymerization of high-molecular-weight organic nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…DNA tells us the quantity of genes related to our enzyme, while RNA tells us its level of activation, offering, therefore, more dynamic information (Malik et al, 2020; Urich et al, 2008). A fruitful field of application of genomic and transcriptomic techniques is the study of biogeochemical cycles, where particular attention has been given to the nitrogen cycle (Séneca et al, 2021). The contribution of these techniques to soil enzymology is nevertheless still relatively limited, mainly due to methodological constraints and the complexity of the relations between gene expression and enzymatic activity (Piotrowska‐Długosz, 2020).…”
Section: Soil Extracellular Enzymesmentioning
confidence: 99%
“…DNA tells us the quantity of genes related to our enzyme, while RNA tells us its level of activation, offering, therefore, more dynamic information (Malik et al, 2020; Urich et al, 2008). A fruitful field of application of genomic and transcriptomic techniques is the study of biogeochemical cycles, where particular attention has been given to the nitrogen cycle (Séneca et al, 2021). The contribution of these techniques to soil enzymology is nevertheless still relatively limited, mainly due to methodological constraints and the complexity of the relations between gene expression and enzymatic activity (Piotrowska‐Długosz, 2020).…”
Section: Soil Extracellular Enzymesmentioning
confidence: 99%
“…The main groups of soil ON compounds are aliphatic-N, including polysaccharide N and amino-N as well as aromatic N, such as those present in soil humus ( Chen and Xu, 2006 ; Talbot and Treseder, 2010 ). These large molecules can be degraded by enzymes of ErM fungi into monomers, such as oligomer, small peptides, and amino acids ( Talbot and Treseder, 2010 ) which are small enough for soil microbes and plants to take up or further mineralize and incorporate as ammonium and nitrate ( Séneca et al., 2021 ). Studies have shown that mycorrhizal fungi and plant roots can take up amino acids.…”
Section: Ericoid Mycorrhizal Fungi Enhance Plant Growthmentioning
confidence: 99%
“…For example, the increased precipitation raised organic P mineralization in soil by favoring phoD bacteria and increased P availability in wet tropical forests (Sun et al., 2020). Considering that rising global temperatures will accelerate SOM decomposition by increasing microbial activity (Séneca et al., 2021), we hypothesize that soil P availability will increase with warming and rising precipitation, especially when combined, due to accelerated microbial mineralization of Po. However, studies on how the abundance of soil PCGs changes with climate factors are rather scarce.…”
Section: Introductionmentioning
confidence: 99%